The difference between clique graphs and iterated clique graphs - de Caria, Pablo Jesús (2011)
Let G be the class of all graphs and K the clique operator. The validity of the equality K(G)=K^2(G) has been an open question for several years. A graph in K(G) but not in K^2(G) is exhibited here.